2014
DOI: 10.1371/journal.pone.0106362
|View full text |Cite
|
Sign up to set email alerts
|

Striatal Astrocytes Act as a Reservoir for L-DOPA

Abstract: L-DOPA is therapeutically efficacious in patients with Parkinson’s disease (PD), although dopamine (DA) neurons are severely degenerated. Since cortical astrocytes express neutral amino acid transporter (LAT) and DA transporter (DAT), the uptake and metabolism of L-DOPA and DA in striatal astrocytes may influence their availability in the dopaminergic system of PD. To assess possible L-DOPA- and DA-uptake and metabolic properties of striatal astrocytes, we examined the expression of L-DOPA, DA and DAT in stria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
52
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 21 publications
6
52
0
Order By: Relevance
“…Also the finding of astrocytic changes in shape and functions in association with DA levels is supported by studies demonstrating that these cells in critical conditions release DA and express enzymes and the complete machinery to metabolize it . Moreover, relevant to PD, astrocytes can manage striatal DA levels, working as a reservoir for circulating levodopa …”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Also the finding of astrocytic changes in shape and functions in association with DA levels is supported by studies demonstrating that these cells in critical conditions release DA and express enzymes and the complete machinery to metabolize it . Moreover, relevant to PD, astrocytes can manage striatal DA levels, working as a reservoir for circulating levodopa …”
Section: Discussionmentioning
confidence: 90%
“…[38][39][40] Moreover, relevant to PD, astrocytes can manage striatal DA levels, working as a reservoir for circulating levodopa. 41 On this view, a different time course in sham-versus 6-OHDA-lesioned rats might reflect different mechanisms (synaptic vs nonsynaptic) by which DA levels change in response to TMS. Taken together, these data suggest that glial cells may have a role in iTBS effects on corticostriatal plasticity.…”
Section: Discussionmentioning
confidence: 99%
“…Given the presence of high concentration of DTT in the lysis buffer and the selective enrichment in aged brains, the quinone modification of GFAP is unlikely a result of the post-lysis artifact. It has been reported that astrocytes will uptake extrcellular DA (Asanuma et al, 2014;Inazu et al, 1999a,b). Therefore, internalized DA may oxidize and modify GFAP in astrocytes, and the accumulation of quinone modified GFAP during aging process may account for the detection of quinone modified GFAP in our study.…”
Section: Discussionmentioning
confidence: 99%
“…In cultured astrocytes from rat cortex, a NET blocker inhibits uptake of dopamine and norepinephrine; the effect was not seen with a DAT blocker, indicating dopamine uptake is performed by NETs in astrocytes (Takeda et al, 2002). In a parkinsonian state, the number of astrocytes increase with dopaminergic denervation (Teismann and Schulz, 2004; Asanuma et al, 2014). Thus, increased NET activity of dopamine transport in the dopamine-denervated striatum may occur at astrocytes, not at norepinephrinergic neurons (Figure 2B).…”
Section: The Role Of Norepinephrine Transporters In Reuptake Of Dopammentioning
confidence: 99%